Advances in Emerging Solar Cells - Batmunkh, Munkhbayar (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Photovoltaic (PV) cells, which directly convert sunlight into electricity, are renewable sources of energy that are sustainable and totally inexhaustible. Emerging classes of solar PV cells have drawn considerable attention because they provide significant advantages over traditional silicon solar cells, such as low cost and attractive designs (lightweight, flexible, and portable) while exhibiting promising performance. Despite these features, certain challenges restrict the possible commercialization of these technologies. The world's leading scientists are making numerous efforts focused on bringing these promising technologies closer to commercialization. Some of these scientists provided valuable research contributions to this Special Issue on "Advances in Emerging Solar Cells" published by Nanomaterials, MDPI. This Special Issue presents 12 excellent articles, 10 research and 2 review papers, covering perovskite solar cells, heterojunction solar cells, organic solar cells, dye-sensitized solar cells, and PV materials. We think that this Special Issue will attract significant attention from a broad research community including renewable energy, photovoltaic, emerging solar cells, material science and nanotechnology.